THE ROLE OF NURSERIES AT THE HOLY SHRINES IN DEVELOPING RECREATIONAL TOURISM (A STUDY OF A SAMPLE OF VISITORS TO THE NURSERIES OF THE HUSSEIN AND ABBASID SHRINES) - Taha Mahdi Mahmood (European Journal of Humanities and Educational Advancements, 2023)
City dwellers perform expensive tasks that are often routine and repetitive, which causes many of them to feel isolated and thus suffer from one of the most important diseases of the era (boredom and alienation). They are deprived of opportunities to communicate and interact with natural resources due to the lack of free time and the distance of natural and recreational resources from their permanent residence and work. Karbala today, after its growth and increase in population, and the continuous tourism and number of permanent visitors throughout the year, which includes main tourist patterns, the most important of which are religious, archaeological, and entertainment, which visitors have begun to pay great attention to as a result of the increase in sites and recreational components that have started to attract them remarkably, most notably the projects of the holy shrines in The city of Karbala, especially the nurseries, has become a significant outlet and worthy of being visited and viewed by a large group of visitors